Case report: A rare case of anti-PD-1 sintilimab-induced agranulocytosis/severe neutropenia in non-small cell lung cancer and literature review - Qin, Yanzhu; Lu, Shuaiji; Chen, Jingwen; Peng, Jing; Yang, Jijun (Frontiers in Oncology, 2024)
Immune checkpoint inhibitors (ICIs) demonstrate unique advantages in the treatment of lung cancer and are widely used in the era of immunotherapy. However, ICIs can cause adverse reactions.Hematological toxicities induced by immunotherapy are relatively rare. Agranulocytosis, a rare hematologic adverse event associated with immune checkpoint inhibitors, has received limited attention in terms of treatment and patient demographics. Herein, we report the case of a 68-year-old male with non-small cell lung cancer(NSCLC) who received two cycles of programmed cell death-1 (PD-1) antibody sintilimab immunotherapy combined with albumin-bound paclitaxel and carboplatin chemotherapy and one cycle of sintilimab monotherapy. He was diagnosed with grade 4 neutropenia and sepsis (with symptoms of fever and chills) after the first two cycles of treatment. Teicoplanin was promptly initiated as antimicrobial therapy. The patient presented with sudden high fever and developed agranulocytosis on the day of the third cycle of treatment initiation, characterized by an absolute neutrophil count of 0.0×10 9 /L. The patient was treated with granulocyte colony-stimulating factor but did not show improvement. He was then treated with corticosteroids, and absolute neutrophil counts gradually returned to normal levels. To the best of our knowledge, this is the first reported case of sintilimab-induced agranulocytosis in a patient with NSCLC. Sintilimab-induced severe neutropenia or agranulocytosis is a rare side effect that should be distinguished from chemotherapy-induced neutropenia and treated promptly with appropriate therapies; otherwise, the condition may worsen.